Biomineralization Induced by Colletotrichum acutatum: A Potential Strategy for Cultural Relic Bioprotection - Li, Tianxiao; Hu, Yulan; Zhang, Bingjian (Frontiers in Microbiology, 2018)
Colletotrichum acutatum is a fungus capable of biomineralization reported in our previous study. In this paper, we compared the ability of this fungus to induce mineralization under different calcium sources, pH levels, and differing carbon availability. Here we found that organic acids, the alkalinity of the environment, and low carbon conditions were major factors influencing calcium carbonate precipitation. High performance liquid chromatography showed that citric acid was a metabolite produced by C. acutatum, and that other organic acids including formic, propionic, α-ketoglutaric, lactic, and succinic acids can be used by this fungus to promote CaCO3 formation. Based on these findings, the mechanism of the biomineralization induced by C. acutatum should be divided into three processes: secreting organic acid to dissolve limestone, utilizing the acid to increase the alkalinity of the microenvironment, and chelating free calcium ions with extracellular polymeric substances or the cell surface to provide a nucleation site. Interestingly, we found that hydroxyapatite rather than calcium carbonate could be produced by this fungus in the presence of phosphate. We also found that the presence of acetic acid could inhibit the transformation of vaterite to calcite. Further, we evaluated whether the proliferation of C. acutatum could influence the deterioration of stone relics. We found that low carbon conditions protected calcium carbonate from dissolution, indicating that the risk of degradation of limestone substrates caused by C. acutatum could be controlled if the fungi were used to consolidate or restore stone monuments. These results suggest that C. acutatum-induced biomineralization may be a useful treatment for deteriorated stone relics.